Fe/N Co-doped TiO2 loaded on functionalized activated carbon fiber for photocatalytic removal of formaldehyde - Liu, Chaojie (2019)
An improved sol-gel method was used to synthesize a new type of photocatalyst Fe/N co-doped TiO2 supported on functionalized activated carbon fiber (ACF), which was applied to catalytically degrade the formaldehyde in the visible light region. The samples were improved by adjusting the amount of hydrolysis water, calcination temperature variation, different pretreatment method for functionalization of ACF and employing different concentration of sodium dodecyl benzene sulfonate (SDBS), which was used as the surfactant for TiO2 particles with a high formaldehyde degradation efficiency up to 75.6% in 120 mins, was obtained. The prepared photocatalysts were characterized via X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and Brunauer-Emmett-Teller specific surface analysis (BET). The SEM analysis showed that TiO2 particles were dispersed uniformly on the surface of ACF. The particles exhibited the anatase structure is the main crystalline phase and rutile also existed with the crystallite diameter of 19.5 and 24.1nm, respectively. In general, this photocatalyst can degrade low concentration of formaldehyde gas with great efficiency under visible light irradiation which is fit for the application of indoor formaldehyde degradation.